IMPLEMENTASI PERATURAN DAERAH KHUSUS (PERDASUS) PROVINSI PAPUA NOMOR 23 TAHUN 2008 TENTANG HAK ULAYAT MASYARAKAT HUKUM ADAT DAN HAK PERORANGAN WARGA MASYARAKAT ADAT ATAS TANAH (STUDI KASUS KOTA JAYAPURA DAN KABUPATEN BIAK NUMFOR) - Ayu Kurnia Utami (Gema Kampus IISIP YAPIS Biak, 2016)
This study discusses Perdasus 23 Year 2008 about individual and communal rights of customary law society over the land through a case study in Jayapura and Biak Numfor. The special local regulation (Perdasus) is a part of the efforts to secure the customary society or the indigenous people of Papua. The aim of this study is to identify how far Perdasus 23 Year 2008 has been implemented in Jayapura and Biak Numfor. The study applies qualitative approach which data is collected through observations, interviews, and content analysis of related documents. The result of this study shows that Perdasus 23 Year 2008 is not implemented thoroughly. Although the regulation is not normatively implemented, it has been practically implemented through the initiatives of Jayapura and Biak Numfor government to carry out conflict resolution program in each region. In doing so, the government of Jayapura has done the communal right mapping of Port Numbay people, while the government of Biak Numfor issues a local regulation (Perbup) about the strategy of land conflict resolution by encouraging of the involvement of customary role and legitimation in the region. Eventhough these activities are not conducted in accordance with Perdasus 23 Year 2008, Jayapura has performed four substances of the “Perdasus”: research, mapping, management and identification, and land conflict resolution. Meanwhile, Biak Numfor regency has performed two substances: communal land management and land conflict resolution though they only fulfill some aspects of these substances when performing research and mapping. There are three aspects affecting the implementation of Perdasus in Jayapura and Biak Numfor. First, ineffective communication both from the policy maker to the policy implementer and from policy implementer to the people that causes confusion to the society regarding the policy. Second, the existing paradigm of local people who still believe that customary law is more powerful than civil law. Last but not the least is Government’s initiative to do an activity to protect the communal right of indigenous people of Papua.